Pengaruh Pelatihan "Pengasuhan Ibu Cerdas" Terhadap Stres Pengasuhan Pada Ibu dari Anak Autis - Hidayati, Fina (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2013)
Past research has shown that parents of children with autism had the highest parenting stress than parents of children with other disabilities. This study aims to determine the effect of training â€œpengasuhan ibu CERdaSâ€ of parenting stress in mothers of children with autism. The study subjects are 20 mothers of children with autism who experience parenting stress from midle to high category, which is divided into an experimental group and control group. The experimental group are 10 people, and the control group are 10 people (waiting list). Training â€œ pengasuhan ibu CERdaS â€œ is given by 7 sessions in the twice meetings. Parenting stress was measured using a scale of PSI (Parenting Stress Index) before being given the training (pretest), administered after training (posttest), and a week after treatment (follow-up). quantitative analysis using statistical techniques of analysis Wilcoxon signed rank (non-parametric) to know the differences between two samples. Based on quantitative data analysis of pretest and posttest measurements of the experiment for the group: the value of Z = -2.499 and 0.012 significance level (p 0.05), indicating a significant decrease in parenting stress in the experimental group after the training is given. Thus training â€œpelatihan ibu CERdaSâ€ could statistically reduce parenting stress in mothers of children with autism.